Creating Excellence in Dementia Care - CAHILL, SUZANNE (My University, 2012)
The estimated cost of formal and informal care for dementia worldwide is currently in excess of 600 billion dollars accounting for 1% of the world?s gross domestic product. This cost, which will grow substantially in the years ahead, is a wake up call for governments around the world prompting more and more of them to develop National Strategies for Dementia. The Irish government gave a commitment in 2010 to develop and implement a Strategy which to be effective must be based on reliable research. The purpose of this research review is to provide the data required by collating estimates of current and future prevalence rates, costs and service provision. It also reviews models of local and international best practice placing an emphasis on those which are person-centred and where the individual is treated as a full citizen with accompanying rights. The research review examines the regional prevalence of dementia in Ireland and estimates the increase in numbers over the next thirty years. This estimation of cost rightly takes both formal and informal care into account, the latter being omitted in many studies. The figures for Ireland match the costs per individual with dementia in other countries and underpin the need for a structured and cost effective approach to dementia in this country. The research review has found that good models of dementia care have been developed in Ireland over the past twenty years but that the level of care provision is very uneven throughout the country with some areas offering little or no support. The review also identifies major deficiencies in the standard of care of individuals with dementia in both acute hospital and long-stay settings. One of the few advantages for Ireland of being a comparatively latecomer in forming a National Dementia Strategy is the opportunity to learn from the achievements and failures of other countries. The evidence presented in this report will be complemented by direct consultation with individuals with dementia and their carers. This research will ultimately form the basis for the creation of a National Dementia Strategy which should be published by government as planned in 2013. Ireland, rather than lagging behind other European countries as at present, could become an international leader in this field in the years ahead going on to fulfil the aspiration of the Taoiseach, Enda Kenny, to make Ireland ?a good place in which to grow old?.
PUBLISHED
Dublin, Ireland
Keywords: Public Health; Dementia